Modulation of eosinophil generation and migration by Mangifera indica L. extract (Vimang (R)) - Sa-Nunes, Anderson; Rogerio, Alexandre P.; Medeiros, Alexandra Ivo de [UNESP]; Fabris, Viciany E.; Andreu, Gilberto P.; Rivera, Dagmar G.; Delgado, Ren; Faccioli, Lucia H. (Elsevier B.V., 2006)
The effects of Vimang((R)), an aqueous extract of the stem bark of Mangifera indica L. (Anacardiaccae), on cell migration in an experimental model of asthma was investigated. In vivo treatment of Toxocara canis-infected BALB/c mice for 18 days with 50 mg/kg Vimang((R)) reduced eosinophil migration into the bronchoalveolar space and peritoneal cavity. Also, eosinophil generation in bone marrow and blood eosinophilia were inhibited in infected mice treated with Vimang((R)). This reduction was associated with inhibition of IL-5 production in serum and eotaxin in lung homogenates. In all these cases the effects of Vimang((R)) were more selective than those observed with dexamethasone. Moreover, Virnang((R)) treatment is not toxic for the animals, as demonstrated by the normal body weight increase during infection. These data confirm the potent anti-inflammatory effect of Vimang R and support its potential use as an alternative therapeutic drug to the treatment of eosinophilic disorders including those caused by nematodes and allergic diseases. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: anti-inflammatory activity; eosinophils; Toxocara canis; Mangifera indica; dexamethasone